IMPLEMENTASI SISTEM AKUNTANSI PEMERINTAHAN DALAM MEWUJUDKAN GOOD GOVERNMENT GOVERNANCE PADA PEMERINTAH PROVINSI SULAWESI UTARA - Manossoh, Hendrik (Sam Ratulangi University, 2015)
ABSTRACT This paper discusses about the implementation of governmental accounting to initiate good governance government at the government of North Sulawesi Province. This paper initially describes about governmental accounting and good government governance. The discussion about governmental accounting includes the background of governmental accounting standard making, description about cash basis toward accrual and accrual basis governmental accounting and the differences between those two accounting basis. The result of this study shows that the implementation of governmental accounting at North Sulawesi province is strongly related to four government governance: fairness, transparency, accountability, and responsibility. Good government governance can be attained with the empowerment of system and institution based on the rules and regulation. Good financial management and control based on governmental accounting system is in the first priority of action that should be taken by the government. Keywords: Governmental Accounting System, Good Government Governance. Â